2014
DOI: 10.1179/1476830514y.0000000156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on psychological and functional outcomes in patients with multiple sclerosis: a cross-sectional study

Abstract: Overweight MS patients evidenced higher depression levels, lower functional capacity, and worse self-rated health status in comparison to normal-weight MS patients. These results suggest that weight control programs should be incorporated into the management of patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
1
14
2
Order By: Relevance
“…[24] Some studies suggested that psychological and gastrointestinal symptoms are more frequent in overweight and obese subjects. [925262730] In line with our study, Berg et al . showed that obese persons report more somatic and psychological symptoms (such as a headache and problem sleeping).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[24] Some studies suggested that psychological and gastrointestinal symptoms are more frequent in overweight and obese subjects. [925262730] In line with our study, Berg et al . showed that obese persons report more somatic and psychological symptoms (such as a headache and problem sleeping).…”
Section: Discussionsupporting
confidence: 92%
“…These findings were consistent with other previous studies. [720212223242526272829] In the Kroenke and Spitzer's study, symptoms such as abdominal pain, back pain, bowel complaints, chest pain, and dizziness were more prevalent in females. [7] Furthermore, Park and Knudson showed the prevalence of somatic symptoms for women was more than twice as those for men.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the previous studies, high BMI and obesity are two of the significant and possible risk factors for MS which have deleterious functional effects on the patients [13][14][15]. In contrast to the previous studies detected childlessness in MS patients [16], the current findings were consistent with a recent pilot study [11].…”
Section: Discussioncontrasting
confidence: 56%
“…Spanish data (NARCOMS study) have shown that overweight people with MS had lower general and mental health scores compared to those with normal weight and found no differences in other quality of life scales of the SF-36 [69].…”
Section: Overweight and Obesitymentioning
confidence: 99%
“…Depression levels were higher in the overweight versus normal weight MS Spanish patients. This finding is due to pathophysiological mechanisms common to both depression and obesity, given that chronic low-grade pro-inflammatory states can generate various abnormalities in different neural networks [69].…”
Section: Overweight and Obesitymentioning
confidence: 99%